L/C basic (Thành phố Hồ Chí Minh, 2009)
The TOEIC ICON series is designed to help you cope with these new challenges. Beginning with the basic level (LC and RC), the TOEIC ICON series introduces basic vocabulary and grammar patterns and provides the users with extensive practice to acquire them.
Keywords: English language,English language,Ngôn ngữ Anh,Ngôn ngữ Anh